PENGARUH PENAMBAHAN BAKTERI (Lactobacillus sp.) DENGAN KONSENTRASI BERBEDA TERHADAP PERTUMBUHAN UDANG VANNAMEI (LitopenaeusVannamei) - Ali Syadillah; Sitti Hilyana; Muhammad Marzuki (Jurnal Perikanan Unram, 2020)
Vaname shrimp has several advantages compared to tiger shrimp that is they are more resistant to disease. Vaname shrimp can be maintained with a very wide salinity range, that is between 0.5-45 ppt.One of the deep problems in vaname shrimp cultivation is the growth of Vaname shrimp which is very slow due to inappropriate management of feed.The purpose of the study is to know the effect of the addition of Lactobacillus sp to the growth of weight, length, SR and FCR Vaname shrimp (Litopanaeus vanamei).This study was conducted using 4 (four) treatments and 3 (three) replications with treatment P1 = (7%), P2 = (9%), P3 = (11%) and P4 = (13%) research location was in Kidang Village and Microbiology Laboratory, Faculty of Agriculture, on April 30-May 13 2019. Plant for 45 days and by measuring the parameters or treatment effects.The results showed that the addition of Lactobacillus sp. as follows,the lowest weight growth is at P1 = P1 = 6,3667±0,17g / head while the highest is in P4 = 7,6±0,23g / head,the lowest weight growth is at P1 = 4,4067±0,41 while P4 = 5,4067±0,12, the lowest SR is at P1 = 76.6% while the highest at P3 = 83.0% and the lowest FCR is at P3 = 2,6067±0,15 while the highest is at P3 = 2,6067±0,15.